Conservative or liberal oxygen therapy in adults after cardiac arrest: An individual-level patient data meta-analysis of randomised controlled trials. (December 2020) - Young, Paul J.; Bailey, Michael; Bellomo, Rinaldo; Bernard, Stephen; Bray, Janet; Jakkula, Pekka; Kuisma, Markku; Mackle, Diane; Martin, Daniel; Nolan, Jerry P.; Panwar, Rakshit; Reinikainen, Matti; et al.
Abstract: Aim: The effect of conservative versus liberal oxygen therapy on mortality rates in post cardiac arrest patients is uncertain. Methods: We undertook an individual patient data meta-analysis of patients randomised in clinical trials to conservative or liberal oxygen therapy after a cardiac arrest. The primary end point was mortality at last follow-up. Results: Individual level patient data were obtained from seven randomised clinical trials with a total of 429 trial participants included. Four trials enrolled patients in the pre-hospital period. Of these, two provided protocol-directed oxygen therapy for 60 min, one provided it until the patient was handed over to the emergency department staff, and one provided it for a total of 72 h or until the patient was extubated. Three trials enrolled patients after intensive care unit (ICU) admission and generally continued protocolised oxygen therapy for a longer period, often until ICU discharge. A total of 90 of 221 patients (40.7%) assigned to conservative oxygen therapy and 103 of 206 patients (50%) assigned to liberal oxygen therapy had died by this last point of follow-up; absolute difference; odds ratio (OR) adjusted for study only; 0.67; 95% CI 0.45 to 0.99; P = 0.045; adjusted OR, 0.58; 95% CI 0.35 to 0.96; P = 0.04. Conclusion: Conservative oxygen therapy was associated with a statistically significant reduction in mortality at last follow-up compared to liberal oxygen therapy but the certainty of available evidence was low or very low due to bias, imprecision, and indirectness. PROSPERO registration number: CRD42019138931.